DARI JALANAN MENUJU LAYAR KACA - Nanang Mizwar Hasyim (Profetik: Jurnal Komunikasi, 2013)
The changer orde baru regime into reformation era has sent the indonesian nation to the process a significant change to the political system and media system, this change has a new basic and support to political live and democratis what is have the freedom feature. The article   “from the streets into the tube”  is a analysis the process of elections journey Indonesia who talk about how the process of change the campaign is traditional campaign to modern style and how the development of style in indonesia campaign ahead. A campaign modern style  is a style compaign who is using persuasive approach, with using mass media as persuasive society and as a complement to the existing campaign conventional style. Besides discuss transforming the campaign, in writing we will take him at in an understanding about how to approachs done by the contestants elections in making political advertising to earn commiserate from society.